Perkembangan Flat Design dalam Web Design dan User Interface (UI) - Dzikri Hasanudin; Oki Adityawan (Pascasarjana ISBI Bandung, 2020)
This writing reveals flat design trends in visual communication design. Visual communication design is how humans communicate with visual images. Every designer has a characteristic in his work. In recent years, flat design has appeared in visual communication design artworks. Many large and well-known companies use flat designs such as Microsoft, Apple, Google, Kompas, and many more. The flat design is very different from the pre-existing flow because it creates simplicity by eliminating all forms of gradation, shadow, glossy, and other effects. It is urged that flat design is the application of a minimalist style and associated it with the Swiss style which was famous in the 1940s to 1950s. In Flat Design, other decorative elements will be seen as unnecessary chaos. If an aspect doesn't serve a functional purpose, it is a distraction to the user experience. This is the reason for the minimalist nature of flat design. However, just because this style doesn't have a flashy design doesn't mean that it will be boring. Bright, contrasting colors illustrate and pop buttons from the background, easily grab attention and catch the user's eye. The goal of a minimalist image also contributes to the functional character of flat design. This paper explains more about the development and application of flat design in visual communication design.Keywords: effect, flat design, graphic, visual communication design.